Potential bioactivities via anticancer, antioxidant, and immunomodulatory properties of cultured mycelial enriched β-D-glucan polysaccharides from a novel fungus Ophiocordyceps sinensis OS8 - Chatnarin, Suwannachom; Thirabunyanon, Mongkol (Frontiers in Immunology, 2023)
Backgroud: Ophiocordyceps sinensis is well-known as a traditional medicine in worldwide. As mycelial cultivation is an alternative source of natural O. sinensis. However, the bioactivities of cultured mycelial enriched β-D-glucan polysaccharides from a novel fungus O. sinensis OS8 are still unknown. Methods: We investigated the potential bioactivities via anticancer, antioxidant and immunomodulatory of polysaccharides (OS8P) produced from cultured mycelia of O. sinensis OS8. This strain is a novel fungus isolated from natural O. sinensis which further cultured by submerged mycelial cultivation for polysaccharide production. Results: The mycelial biomass yield was 23.61 g/l with adenosine content and polysaccharide yield of 306.1 mg/100 g and 3.22 g/100 g, respectively. These OS8P were enriched with β-D-glucan at the rate of 56.92% and another form of α-D-glucan was 35.32%. The main components of OS8P were dodecamethyl pentasiloxane, 2,6-bis (methylthiomethyl) pyridine, 2-(4-pyrimidinyl)-1H-Benzimidazole and 2-Chloro-4-(4-nitroanilino)-6-(O-toluidino)-1,3,5-triazine at the rates of 32.5, 20.0, 17.5 and 16.25%, respectively. The OS8P significantly inhibited the proliferation of colon cancer cells (HT-29), with IC50 value of 202.98 µg/ml and induced apoptosis in HT-29 cells as confirmed by morphological change analysis via AO/PI and DAPI staining, DNA fragmentation and scanning electron microscopic observations. The OS8P showed significance in DPPH radical scavenging and ABTS radical cation scavenging activities, with IC50 values 0.52 and 2.07 mg/ml, respectively. The OS8P also exhibited good immunomodulatory activities. It showed positive and direct correlation with the concentration of the OS8P that significantly enhanced (P < 0.05) the induction of splenocyte proliferation. Conclusion : The OS8P enriched with β-D-glucan polysaccharides and produced by submerged mycelial culture of new fungal strain of O. sinensis OS8 strongly inhibited the growth of colon cancer cells without any cytotoxicity against normal cells. The inhibitory effect of the OS8P on the growth of cancer cells was mainly due to the induction of apoptosis. The OS8P exhibited good antioxidant and immunomodulatory activities. These findings suggest that OS8P has potential applications on functional food industry and/or therapeutic agent for colon cancer.